Prosecution of Wartime Environmental Damage by Non-State Parties at the International Criminal Court - Jessica Schaffer (Bond Law Review)
This article presents a novel way of prosecuting wartime environmental damage committed by non-state parties to the Rome Statute at the International Criminal Court. The current legal framework applicable during armed conflicts has many gaps and weaknesses, leaving the environment as a silent victim. The stringent threshold that must be met before environmental damage is prohibited under international humanitarian law has failed to offer any real protection, particularly in non-international armed conflicts, despite their growing prevalence. Furthermore, destruction of the environment has not materialised as a distinct crime in international law; rather, it is treated as a material element or underlying act of other crimes in the Rome Statute. Where states involved in armed conflicts are not party to the Rome Statute, individuals can seemingly enjoy impunity for serious environmental harm arising during the conflict. This article will illustrate how individuals from non-state parties could face criminal responsibility for environmental crimes where one element of the crime, namely environmental damage, is committed on the territory of a state party. This offers a novel, albeit limited route for addressing the gaps in the current law.